NEXUS BETWEEN CORPORATE GOVERNANCE, CAPITAL STRUCTURE, AND MARKET VOLATILITY ON CORPORATE FINANCIAL PERFORMANCE - Hafsa Khan; Dr Shahan Zeb Khan; Dr Fawad Ali Khan; Kamaran Qader Yaqub; Sudhair Abbas Bangash (Policy Research Journal, 2024)
This study investigates the effects of corporate governance, capital structure, and market volatility on corporate financial performance, utilizing secondary data across multiple industries. Corporate governance is assessed through board composition, ownership structure, and regulatory compliance, emphasizing its role in fostering transparency, accountability, and long-term value creation. Capital structure, evaluated through key financial metrics such as debt-to-equity ratios and overall leverage, is examined to understand how a firm's financing decisions impact its financial health and growth prospects. Market volatility, an external factor, is derived from historical stock market data and macroeconomic variables, providing insight into how unpredictable market conditions influence corporate performance. By using secondary data from publicly listed firms, this study applies advanced statistical techniques to analyze the relationship between these independent variables and corporate financial performance. The findings will offer valuable insights for policymakers, corporate managers, and investors, highlighting the importance of sound governance practices, optimal capital structuring, and adaptability in volatile markets. This research contributes to the growing body of literature by emphasizing how internal and external dynamics shape the financial outcomes of corporations, ultimately guiding strategic financial decision-making.